2010
DOI: 10.3109/02699051003709607
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about brain injury in Britain

Abstract: Primary objective: Surveys have revealed that a high proportion of the public in the US and Canada hold misconceptions pertaining to the sequelae of brain injury. This study examined whether similar misconceptions are endorsed by adults in Britain.Research design: Survey Methods and procedures: Three hundred and twenty two participants completed a 17 item questionnaire containing true or false statements about general knowledge of brain injury, coma and consciousness, memory impairments and recovery.Main outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 12 publications
5
45
0
Order By: Relevance
“…The categories that showed the most misconceptions were amnesia (49.7%) and unconsciousness (46.1%). Generally, these findings appear to be comparable to the findings of Hux et al [1] and Chapman and Hudson, [15] which also indicated misconception rates ranging from 43.8% to 60.6% for amnesia and 54.7% to 63.4% for unconciousness, and that these 2 categories bore the most misconceptions. Participants had the fewest misconceptions in the brain damage category (8.4%), which is similar to the findings of Hux et al [1] (8.3%) and Ernst et al [13] (6.6%).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The categories that showed the most misconceptions were amnesia (49.7%) and unconsciousness (46.1%). Generally, these findings appear to be comparable to the findings of Hux et al [1] and Chapman and Hudson, [15] which also indicated misconception rates ranging from 43.8% to 60.6% for amnesia and 54.7% to 63.4% for unconciousness, and that these 2 categories bore the most misconceptions. Participants had the fewest misconceptions in the brain damage category (8.4%), which is similar to the findings of Hux et al [1] (8.3%) and Ernst et al [13] (6.6%).…”
Section: Discussionsupporting
confidence: 78%
“…Generally, these findings are in keeping with previous literature, which suggests that misconceptions about TBIs are common among the general population. [1,13,15] Some misconceptions appear to be more common than others. Examples of the more common misconceptions include the belief that when people are knocked unconscious, most will wake up quickly with no lasting effects (54% v. rates ranging from 48.11% to 59.28% in previous studies), [1,11] and the misconception that the primary goal of brain injury rehabilitation is to increase physical abilities such as walking (51.1% v. 65.5% in previous studies).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may further perpetuate the belief that traits such as increased aggression, a lack of empathy, or difficulty in adhering to programmes, such as those mandated by the court, are simply the fault of the Hudson examining misconceptions among the British public asked respondents to comment on where they had learned about brain injury (27). Of the 301 participants who responded to this question, 38%…”
Section: Discussionmentioning
confidence: 99%